A new species of early-diverging Sauropodiformes from the Lower Jurassic Fengjiahe Formation of Yunnan Province, China - Claire Peyre de Fabrègues (Nature Portfolio, 2020)
Abstract Sauropodomorpha were herbivorous saurischian dinosaurs that incorporate Sauropoda and early-diverging sauropodomorphs. The oldest sauropodomorph remains are known from Late Triassic deposits, most of them Gondwanan. The Laurasian record comprises some Triassic forms, but the bulk is Jurassic in age. Among the 14 Jurassic non-sauropodan sauropodomorphs from Laurasia described in the past, 8 are from China. Here we describe a new non-sauropodan sauropodomorph, Irisosaurus yimenensis gen. et sp. nov., from the Early Jurassic Fengjiahe Formation of China. Nearly all of the non-sauropodan sauropodomorph genera currently known from China were first reported from the Lufeng Formation. The Fengjiahe Formation is its Southern equivalent, bringing a fauna similar to that of the Lufeng Formation to light. The new genus is defined based on an incomplete but unique maxilla, with a premaxillary ramus higher than long prior to the nasal process, a large and deep neurovascular foramen within the perinarial fossa, and a deep perinarial fossa defined by a sharp rim. Phylogenetic analysis places Irisosaurus at the very base of Sauropodiformes, as the sister-taxon of the Argentinean genus Mussaurus. This specimen adds to a growing assemblage of Chinese Jurassic non-sauropodan sauropodomorphs that offers new insight into the Laurasian evolution of this clade.